2011
DOI: 10.1007/s12265-011-9288-9
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineering the Infarcted Heart by Applying Bio-inspired Materials

Abstract: Induction of cardiac muscle regeneration following myocardial infarction (MI) represents a major challenge in cardiovascular therapy, as the current clinical approaches are limited in their ability to regenerate a new muscle tissue and to replace infarcted myocardium. Here, we describe the conception of two strategies based on bio-inspired materials, aimed at myocardial repair after MI. In the first strategy, alginate biomaterial was designed with affinity-binding moieties, enabling the binding of heparin-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 112 publications
(106 reference statements)
0
19
0
Order By: Relevance
“…This hypothesis was confirmed by numerous studies showing that the CM, collected from a variety of stem cell populations, had beneficial effects on cells and tissues in vitro and in vivo [3,24]. These studies showed that various stem/ progenitor cell populations, such as MSCs or EPCs, released proangiogenic and antiapoptotic cytokines in culture, which may contribute to enhanced angiogenesis and endogenous repair [25]. However, for the stem cell-secreted factors to be useful in cell therapy for efficient vascular repair, more research is needed to identify the mechanisms by which they affect vasculogenesis.…”
Section: Discussionmentioning
confidence: 65%
“…This hypothesis was confirmed by numerous studies showing that the CM, collected from a variety of stem cell populations, had beneficial effects on cells and tissues in vitro and in vivo [3,24]. These studies showed that various stem/ progenitor cell populations, such as MSCs or EPCs, released proangiogenic and antiapoptotic cytokines in culture, which may contribute to enhanced angiogenesis and endogenous repair [25]. However, for the stem cell-secreted factors to be useful in cell therapy for efficient vascular repair, more research is needed to identify the mechanisms by which they affect vasculogenesis.…”
Section: Discussionmentioning
confidence: 65%
“…that can bind and sequester growth factors (59) or contain fragments that influence cell recruitment (e.g. Fibrin fragment E is thought to contain angiogenic products).…”
Section: Current Exploration Of Acellular Hydrogel Mechanisms Of Actionmentioning
confidence: 99%
“…5c) (68). These immunomodulatory effects of liposomes are now actively pursued as a way of increasing adjuvanicity of vaccines (69) or attenuating inflammation (70)(71)(72).…”
Section: Polar Lipidsmentioning
confidence: 99%